Monodispersed calcium carbonate nanoparticles modulate local pH and inhibit tumor growth in vivo. Issue 25 (8th January 2016) - Som, Avik; Raliya, Ramesh; Tian, Limei; Akers, Walter; Ippolito, Joseph E.; Singamaneni, Srikanth; Biswas, Pratim; Achilefu, Samuel
Abstract : Intravenously administered CaCO3 nanoparticles can induce tumor growth inhibition via local increases in tumor extracellular pH in vivo . Abstract : The acidic extracellular environment of tumors potentiates their aggressiveness and metastasis, but few methods exist to selectively modulate the extracellular pH (pHe) environment of tumors. Transient flushing of biological systems with alkaline fluids or proton pump inhibitors is impractical and nonselective. Here we report a nanoparticles-based strategy to intentionally modulate the pHe in tumors. Biochemical simulations indicate that the dissolution of calcium carbonate nanoparticles (nano-CaCO3 ) in vivo increases pH asymptotically to 7.4. We developed two independent facile methods to synthesize monodisperse non-doped vaterite nano-CaCO3 with distinct size range between 20 and 300 nm. Using murine models of cancer, we demonstrate that the selective accumulation of nano-CaCO3 in tumors increases tumor pH over time. The associated induction of tumor growth stasis is putatively interpreted as a pHe increase. This study establishes an approach to prepare nano-CaCO3 over a wide particle size range, a formulation that stabilizes the nanomaterials in aqueous solutions, and a pH-sensitive nano-platform capable of modulating the acidic environment of cancer for potential therapeutic benefits.